Status of the PSF Reconstruction Work Package for MICADO@ELT - Grazian Andrea; Simioni Matteo; Arcidiacono Carmelo; Achren Jani; Clenet Yann; Cao Yixian; Davies Richard; Gullieuszik Marco; Helin Tapio; Jodlbauer Daniel; Kuncarayakti Hanindyo; Le Louarn Miska; et al. (United States, 2025)
MICADO is a workhorse instrument for the ESO ELT, allowing first light capability for diffraction limited imaging and long-slit spectroscopy at near-infrared wavelengths. The PSF Reconstruction (PSF-R) Team of MICADO is currently implementing, for the first time within all ESO telescopes, a software service devoted to the blind reconstruction of the PSF. This tool will work independently of the science data, using adaptive optics telemetry data, both for Single Conjugate (SCAO) and Multi-Conjugate Adaptive Optics (MCAO) allowed by the MORFEO module. The PSF-R service will support the state-of-the-art post-processing scientific analysis of the MICADO imaging and spectroscopic data. We provide here an update of the status of the PSF-R. service tool of MICADO, after successfully fulfilling the Final Design Review phase, and discuss recent results obtained on simulated and real data gathered on instruments similar to MICADO.
Proceedings of SPIE: Adaptive Optics Systems VIII